ALIGNMENT DAN ANALISIS KEKERABATAN RAYAP COPTOTERMES FORMOSANUS (Isoptera: Rhinotermitidae) PADA HABITAT YANG BERBEDA DENGAN SOFTWARE BIOEDIT DAN MEGA 6 (STUDI PUSTAKA DNA SEKUENSING DARI NCBI) - Leiwakabessy, Fredy; Awan, Ali; Kubangun, Muhammad Tarmizi; Pattiasina, Eifan Boyke (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: Bioinformatics is a science that can relate information which includes molecular biology, biochemical structure, enzymatic, cell biology, physiology and pathology by using a computerized system based on data that has been collected. Methods: sequence alignment and phylogenetic tree construction of DNA sequences registered at NCBI in the subterranean termite Coptotermes formosanus Shiraki that lives in different habitats, namely in Mississippi, Southeast Asia, and China using Bioedit and MEGA software. Results: Sequence alignment showed that termite C. formosanus isolated from MS12 gene COII (FJ870577.1) in the Mississippi area had a base pair of 790 bp, termite C. formosanus isolated from Dinghu Mountain gene COII (KU257993.1) in China has a base pair of 779 bp, and the termite C. formosanus isolated from CF003JP gene COII (EF379943.1) in Southeast Asia has a base pair of 676 bp. The construction of the phylogenetic tree shows that the termite C. formosanus isolated from Dinghu Mountain gene COII (KU257993.1) in the China region has a close kinship with the termite C. formosanus isolated from CF003JP gene COII (EF379943.1) in the Southeast Asia region, while The termite C. formosanus isolated from MS12 gene COII (FJ870577.1) in the Mississippi area is distantly related to C. formosanus (KU257993.1) from China and C. formosanus (EF379943.1) from Southeast Asia. Conclusion: Mississippi has a base pair of 790 bp, termite C. formosanus isolated from Dinghu Mountain gene COII (KU257993.1), China has a base pair of 779 bp, and termite C. formosanus isolated from CF003JP gene COII (EF379943.1), Southeast Asia has a base pair of 676 bp. China is closely related to the termite C. formosanus isolated from COII gene CF003JP (EF379943.1), Southeast Asia, while the termite C. formosanus isolated from MS12 gene COII (FJ870577.1), Mississippi is distantly related to C. formosanus (KU257993.1) from China and C. formosanus (EF379943.1) from Southeast Asia.